F1F0-ATP Synthase Inhibitory Factor 1 in the Normal Pancreas and in Pancreatic Ductal Adenocarcinoma: Effects on Bioenergetics, Invasion and Proliferation - Tanton, Helen; Voronina, Svetlana; Evans, Anthony; Armstrong, Jane; Sutton, Robert; Criddle, David N.; Haynes, Lee; Schmid, Michael C.; Campbell, Fiona; Costello, Eithne; Tepikin, Alexei V. (Frontiers in Physiology, 2018)
F1F0-ATP synthase inhibitory factor 1 (IF1) inhibits the reverse mode of F1F0-ATP synthase, and therefore protects cellular ATP content at the expense of accelerated loss of mitochondrial membrane potential (ΔΨm). There is considerable variability in IF1 expression and its influence on bioenergetics between different cell types. High levels of IF1 in a number of cancers have been linked to increased glycolysis, resistance to cell death, increased migration and proliferation. However, neither the expression nor role of IF1 in the normal pancreas or in pancreatic cancer has been characterised. In this study, we found that pancreatic ductal adenocarcinoma (PDAC) patients express higher levels of IF1 in cancerous cells than in pancreatic acinar cells. PDAC cell lines have a higher IF1 content and IF1/ATP synthase ratio than pancreatic acinar cells. The observed differences are consistent with the ability of the respective cell types to maintain ΔΨm and ATP levels in conditions of chemical hypoxia. Acinar cells and PDAC cells preferentially express different IF1 isoforms. Both knockdown and knockout of IF1 in the PANC-1 pancreatic cancer cell line modified cellular bioenergetics and decreased migration, invasion and proliferation suggesting the putative importance of IF1 for PDAC growth and metastasis.